Lasers and non linear optics Ed 4 - B B Laud (New Delhi New Age International, 2025)
The book is addressed to the advanced undergraduate and postgraduate students interested in lasers. It encompasses the wide area joining laser physics and nonlinear optics. Earlier chapters give a concise account of basic physics on which the operation of lasers depend. Quantum mechanical treatment of the interaction of radiation with an atom and of some important optical processes is presented. This prepares the way, by easy stages, for the formal development of lasers. The advances in laser physics over the last twenty-five years are described. The material in non-linear optics scattered in various journals is collected in a compact and unified manner. Some research problems of current interest are discussed. The treatment is kept as simple as possible so that students may not have any difficulty with it. The book will help the readers to acquire new concepts and advanced methods in non-linear optics and give them a sort of overall perspective necessary to continue further independent research. The book will be beneficial to a variety of readers.
Keywords: Einsteins Quantum Theory of Radiation; Masers; Laser Spectroscopy